2014
DOI: 10.1093/infdis/jiu676
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cytokines With Exosomes in the Plasma of HIV-1–Seropositive Individuals

Abstract: Human immunodeficiency virus (HIV)-infected and viremic individuals exhibit elevated levels of plasma cytokines. Here we show that most cytokines are not in free form but appear associated with exosomes that are distinct from virions. Purified exosomes were analyzed to determine the levels of 21 cytokines and chemokines and compared with exosome-depleted plasma. Most cytokines were markedly enriched in exosomes from HIV-positive individuals relative to negative controls and to plasma. Moreover, exposure of nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 14 publications
(20 reference statements)
3
86
0
Order By: Relevance
“…6 ). Nevertheless, we also expect EVs to carry many other proliferative miRNAs, as observed in small-RNA seq analysis, along with proteins and transcription factors (19, 79) such as HIF-1α, cytokines (80), and growth factors that may contribute to enhanced proliferation of cells. Overall, our study underscores the role of communication between HIV-1–infected inflammatory cell–derived EVs and uninfectable pulmonary vascular cells in HIV PAH pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Nevertheless, we also expect EVs to carry many other proliferative miRNAs, as observed in small-RNA seq analysis, along with proteins and transcription factors (19, 79) such as HIF-1α, cytokines (80), and growth factors that may contribute to enhanced proliferation of cells. Overall, our study underscores the role of communication between HIV-1–infected inflammatory cell–derived EVs and uninfectable pulmonary vascular cells in HIV PAH pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…55 A recent study demonstrated that exosomes are also enriched in cytokines in the plasma of HIV-positive individuals relative to the negative controls. 56 These studies provide a basis for exosomes as biomarkers for HIV infection. Elegant work from the study by Sampey et al 137 using hydrogel nanotrap particles as affinity baits, has demonstrated the capture of HIV-1 virions, HIV proteins and exosomes-containing TAR-RNA in the patient serum.…”
Section: Hiv Infection Alters Exosomal Release and Compositionmentioning
confidence: 96%
“…Plasma was collected from whole blood of human donors into tubes containing ethylenediaminetetraacetic acid (EDTA) and processed as described by Konadu et al 23 with some modifications. Whole-blood samples were centrifuged at 3,500 rpm for 10 min at 4°C.…”
Section: Isolation Of Human Plasma-derived Exosomesmentioning
confidence: 99%
“…We also isolated exosomes from human breast milk and human plasma using published methods. 15,23 To confirm successful exosome isolation, we performed a series of SDS-PAGE and Western blot analyses to examine expression of well-known exosomal proteins ( Figure 1A and B). Specifically, breast milk exosomes incubated with anti-clathrin and -CD9 antibodies yielded protein bands at 180 kDa and 28 kDa, respectively ( Figure 1A1 and A2).…”
Section: Isolation and Characterization Of Exosomesmentioning
confidence: 99%